Peran Budaya Organisasi Sebagai Variabel Intervening dalam Hubungan Psychological Capital dan Leadership Challenge Terhadap Work Happiness pada PT Konecranes Material Handling Indonesia - Rahmat Mulia Siregar; Siti Safaria (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2026)
The purpose of this study is to analyze the role of organizational culture as a mediating variable in the relationship between psychological capital and leadership challenge on employee work happiness. This study was conducted at a foreign company based in Singapore that has a subsidiary in Indonesia, namely PT Konecranes Material Handling Indonesia using primary data which is questionnaire with Likert measurement scale (1-5), distributed to 120 respondents who had been previously selected using non-probability sampling techniques that are classified as census and using secondary data in the form of observation methods, interviews and literature review. This research was conducted using descriptive analysis of respondent characteristics and path coefficient between variables. The method used in this study is partial least square (SmartPLS). From the result of data processing, it is known that there is a significant influence between psychological capital and leadership challenge on organizational culture positively. Organizational culture has directed influence on work happiness. The next finding was found that there was no influence between psychological capital and leadership challenge on work happiness directly but there is influence between them on work happiness indirectly through organizational culture.